Hedgehog pathway inhibitors (HHI) combined with radiotherapy and immunotherapy for advanced basal cell carcinoma: a case report - Zhuren Ruan; Chen Zhao; Longshan Li; Xianghui Li; Zhijian Yao; Gao Wei (Journal of Dermatological Treatment)
Purpose Basal cell carcinoma (BCC) is one of the most common skin cancers. Most BCCs can be treated with surgery excision. For advanced BCC unsuitable for curative surgery, the combination of radiotherapy and Hedgehog pathway inhibitors (HHI) are effective systemic treatment options. However, there is a scarcity of evidence-based guidelines for the management of patients with advanced or metastatic BCC, particularly those who develop resistance to HHI therapy.Materials and methods We report the case of a patient with advanced BCC of the head and neck, which originated from a nevus sebaceous.Results The patient initially responded well to sonidegib, an HHI, but resistance emerged within a month. We then modified the systemic therapy to include a combination of radiotherapy and the anti-PD-1 agent sintilimab.Conclusions This adjusted treatment regimen led to effective long-term clinical responses without significant adverse events.